A multiple case study to understand how students experience science and engineering practices - Chris Schaben; Justin Andersson; Christine Cutucache; Christine Cutucache (Frontiers in Education, 2022)
The Next Generation Science Standards (NGSS), amid recent shifts in science curriculum, call for students to learn science through the practices of scientists and engineers (science and engineering practices, or SEPs). SEPs, related to inquiry learning, are ways students learn science content by doing science. Students have varied experiences learning science and engineering practices, including exposure in the classroom, from media, and in science fairs. Using a qualitative, multiple case study design, we analyzed public school educators’ and middle and high school students’ (ages 12–18) interview transcripts about learning through the science and engineering practices. Findings demonstrate that students learn different aspects of science and engineering practices during both in school and out-of-school science learning. Several transcending themes emerged from our interview data leading to recommendations for educators. Specific science and engineering practices might be better leveraged to introduce students to scientific research, students saw themselves as scientists leading to development of science identity while learning through SEPs, the relevancy of their work drove student learning, and resiliency was important during many of their learning experiences.